The impact of role-playing games through Second Life on the oral practice of linguistic and discursive sub-competences in English - Quintín Linero, Eliana Maritza; Sanz, Cecilia Verónica; Zangara, María Alejandra (2016)
This paper describes a case study, carried out in an educational setting, whose purpose includes the analysis of the impact that role-playing games (RPGs), with the mediation of the immersive virtual environment Second Life, causes in the oral practice of linguistic and discursive communicative subcompetences in English. It is discussed an interdisciplinary participation of the communicative approach of languages, the technologies involved in the development of this study, RPGs and task-based learning. The study outlines the phases that make up the experience, the categories of analysis addressed from the triangulation of data collected, and finally the conclusions and future research.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
2016 International Conference on Collaboration Technologies and Systems (2016 : Orlando, Estados Unidos)
Keywords: EDUCACIÓN; VIDEOJUEGOS